(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
In today’s ever-changing technological era, the innovative and improvising advancements has facilitated the digital payments progressively and has become the most prominent constituent of financial literacy in the midst of the women’s society. This study aims at determining the factors which affects the level of financial literacy of women towards digital payments. The ten selected influencing factors of women’s financial literacy are identified from the study of literature. Interpretive Structural Modelling (ISM) and MIC-MAC approach has been applied to test how one factor’s impact the other influencing factor. The outcomes of the study makes the valuable contribution to researchers in the terrain of behavioural finance and advancement of technical era as well as growth of financial literacy.